Kajian Risiko pada Proses Penyimpanan dan Pendistribusian Bahan Baku di Gudang Industri Farmasi dengan Pendekatan Metode Failure Mode and Effect Analysis - Hanif Azhar Musyaffa; Mas Rahman Roestan; Evi Sylvia Nurrasjid; Iwa Kustiyawan (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Quality risk management is one of the important things in quality control in a pharmaceutical industry. One of the risky activities in the pharmaceutical industry is in storage and distribution. Every activity carried out in the inventory warehouse can potentially cause risks that affect quality including the flow of the storage and distribution process of goods. Based on this, a study was conducted in the form of a risk assessment on the flow of the storage and distribution process of release goods in the inventory warehouse of a pharmaceutical industry in Bandung which aims to determine the level of risk that has the potential for failure. The FMEA (Failure Modes and Effects Analysis) method is a method that can be used to assess the risks that can occur in the flow of the storage and delivery process of goods in the warehouse. This risk assessment is carried out with the stages of risk identification, risk analysis, and risk evaluation using categorization based on the Risk Priority Number (RPN). In this study, 15 risks were obtained with details of 1 low category risk, 7 medium category risks, 6 high category risks, and 1 very high category risk. Therefore, the pharmaceutical industry can immediately determine mitigation steps and take control measures against risks in the high and very high categories to reduce the risk of failure with the hope that the quality, safety and efficacy of the product can be maintained properly